A study on the production and marketing of tuba in Sitio Bukid, Brgy. Calingcaguing, Barugo, Leyte - Buñales, Eden Astorga (2001)
This study sought to describe the tuba industry in Sitio Bukid, Barangay Calingcaguing, Barugo, Leyte. It aimed to determine the demand and supply of tuba, identify the problems encountered in production and marketing of tuba and suggest or recommend ways that will improve the industry.
This paper focused on the tuba gatherers in the aforementioned locality. A survey was made using the questionnaire as the instrument in gathering the data.
This study revealed that the demand for tuba is high during the months of October to December and the supply of tuba is abundant during the month of August.
Undergraduate thesis (B.A.S.S. Economics) -- University of the Philippines, Tacloban.
Keywords: Demand and supply